2016
DOI: 10.1155/2016/4567580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Role of EGFR-MAPK Pathway in Patchouli Alcohol-Induced Apoptosis and Cell Cycle Arrest on A549 CellsIn VitroandIn Vivo

Abstract: Nowadays, chemotherapy is still the main effective treatment for cancer. Herb prescriptions containing Pogostemon cablin Benth (also known as “Guang-Huo-Xiang”) have been widely used in Chinese medicine today. In our research, we found that patchouli alcohol, a compound isolated from the oil of Pogostemon cablin Benth, exerted antitumor ability against human lung cancer A549 cells ability both in vitro and in vivo. MTT assay was used to assess cell viability. Hoechst 33342 staining and TUNEL cover glass staini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Another component, α -guaiene, was found to be responsible for most of the cytotoxic activity of Bulnesia sarmientoi against A549 and H661 lung cancer cells [ 38 ]. Exposure of HCT116 and SW480 colorectal cancer cells to patchouli alcohol activated p21 expression and inhibited the expression of cyclin D1 and CDK4 and induced cell apoptosis and cell cycle arrest in A549 lung cancer cells in vitro and in vivo via the EGFR-MAPK pathway [ 39 , 40 ]. A hexane fraction of guava leaves ( Psidium guajava L.), which contained 3.76% α -patchoulene, inhibited the AKT/mTOR/S6K1 signaling pathway and induced apoptosis in prostate cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another component, α -guaiene, was found to be responsible for most of the cytotoxic activity of Bulnesia sarmientoi against A549 and H661 lung cancer cells [ 38 ]. Exposure of HCT116 and SW480 colorectal cancer cells to patchouli alcohol activated p21 expression and inhibited the expression of cyclin D1 and CDK4 and induced cell apoptosis and cell cycle arrest in A549 lung cancer cells in vitro and in vivo via the EGFR-MAPK pathway [ 39 , 40 ]. A hexane fraction of guava leaves ( Psidium guajava L.), which contained 3.76% α -patchoulene, inhibited the AKT/mTOR/S6K1 signaling pathway and induced apoptosis in prostate cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol might have increased the shedding of EGFR molecules into the bloodstream. Lu et al [23] demonstrated that alcohol could be associated with apoptosis and EGFR degradation in lung cancer cell line. However, further studies are warranted to clarify this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Patchouli alcohol, isolated from the essential oil of Pogostemon cablin, induced mitochondria-mediated apoptosis and caspase-9 and caspase-3 production in A549 cells [ 327 ]. The oil may also demonstrate its anticancer activity by dysregulating the MAPK pathway.…”
Section: The Lamiaceae Family Plantsmentioning
confidence: 99%